Sustainable P-enriched biochar-compost production: harnessing the prospects of maize stover and groundnut husk in Ghana’s Guinea Savanna - Fianko, Daniel A.; Nartey, Eric K.; Abekoe, Mark K.; Adjadeh, Thomas A.; Lawson, Innocent Y. D.; Amoatey, Christiana A.; Sulemana, Nasirudeen; Akumah, Asiwome M.; Baba, Mutala E.; Asuming-Brempong, Stella (Frontiers in Environmental Science, 2023)
Farmers in resource-poor areas of the Guinea Savanna zone of Ghana often face declining soil fertility due to the continuous removal of nutrient-rich harvested produce from their fields. This study focuses on the Lawra Municipality in the Guinea Savannah zone of Ghana, where low soil fertility, specifically limits phosphorus (P) bioavailability and hinders crop production. The objective of this research is to formulate P-enhanced biochar-compost from farm residuesmaize stover and groundnut husk to which abound in the area sustainably replenish soil fertilityimprove P availability in smallholder farmer fieldssoils of northern Ghana to close the nutrient loop. Maize stover was co-composted with groundnut husk biochar at varying rates of (0, 10, 20, 30, and 40% by volume). To facilitate decomposition using the windrow system, the composting heaps were inoculated with decomposing cow dung, and moisture content kept at 60% throughout the monitoring period. The addition of biochar shortened the lag phase of composting. However, rates above 20% resulted in reduced degradation of maize stover. Biochar incorporation enriched available phosphorus content in the final compost from 286.7 in the nonbiochar-compost to 320, 370, 546 and 840.0 mg kg -1 in the 10%, 20%, 30% and 40% biochar-compost respectively. The 20%, 30% and 40% biochar compost types have ideal properties for use as soil amendment for improved legume production for biological N fixation and carbon sequestration.